1995
DOI: 10.3354/meps126293
|View full text |Cite
|
Sign up to set email alerts
|

Bacterioplankton viability in Antarctic waters as affected by solar ultraviolet radiation

Abstract: The effect of solar ultraviolet radiation (UVR) on viability of natural bactenoplankton assemblages from Antarctic waters, as well as on 2 cultures of isolated bacterial strains (Acinetobacter sp. and BaciUus sp.), was determined by both in situ and temperature-controlled incubator experiments. When natural assemblages were incubated in situ at 0.5 m depth, the mean percentage survival fractions (of the bacteria forming colonies on agar) were 13% when the sample was exposed to all UVR, 27 % when UV-B radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 11 publications
4
32
1
Order By: Relevance
“…Morán et al (2001) reported that PAR inhibited bacterial activity whereas Sommaruga et al (1997) reported that PAR and UVR have equally inhibitory effects on the rates of both [methyl-3H]-thymidine (TdR) and 14 C-leucine (Leu) utpake in bacteria in the Adriatic Sea. Aas et al (1996) found that PAR in the Gulf of Mexico can actually stimulate bacterial uptake of both tracers, while Helbling et al (1995) reported that PAR radiation has no effect on bacterial growth in the Antarctic waters.…”
Section: Introductionmentioning
confidence: 99%
“…Morán et al (2001) reported that PAR inhibited bacterial activity whereas Sommaruga et al (1997) reported that PAR and UVR have equally inhibitory effects on the rates of both [methyl-3H]-thymidine (TdR) and 14 C-leucine (Leu) utpake in bacteria in the Adriatic Sea. Aas et al (1996) found that PAR in the Gulf of Mexico can actually stimulate bacterial uptake of both tracers, while Helbling et al (1995) reported that PAR radiation has no effect on bacterial growth in the Antarctic waters.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton and primary production have been the focus of the majority of previous studies (Bidigare 1989, Marchant et al 1991, Holm-Hansen et al 1993, Schick et al 1995, Forster & Lüning 1996, Herrmann et al 1997, Holm-Hansen 1997, Zagarese et al 1997, while significantly less is known about UV radiation effects on bacterioplankton in the Southern Ocean. Helbling et al (1995) reported that viability, based on colony-forming units (CFU), of a natural bacterial assemblage and 2 marine isolates from Antarctic waters decreased significantly when exposed to UV-R. The inhibition of viability due to UV-A was consistently higher than UV-B in all cases, but, interestingly, there were marked differences in the tolerance of the natural assemblage and the 2 isolates to solar radiation, suggesting a heterogeneity in sensitivity among species.…”
mentioning
confidence: 99%
“…Undoubtedly, various residents of the marine microbial community have different tolerances and defenses to solar UV radiation (Helbling et al 1995, Joux et al 1999, Arrieta et al 2000. RM11001 must tolerate different periods of UV radiation during the Antarctic spring and summer and as a result of thinning ozone than does the sub-tropical Vibrio natriegens isolate.…”
Section: General Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santas et al 1998, Helbling et al 2001 and references therein), bacterioplankton (e.g. Helbling et al 1995, Jeffrey et al 1996, Kaiser & Herndl 1997, Gustavson et al 2000, zooplankton (e.g. Chiang et al 2003) and the marine community as whole (e.g.…”
Section: Introductionmentioning
confidence: 99%